Management of missing incisor with tooth malposition using removable orthodontic appliances and modified design adhesive bridge: a case report - Marshaliana, Cindy Lestari; Sinaga, Valentine Rosadi; Bonifacius, Setyawan; Novianti, Vita Mulya Passa (Padjadjaran Journal of Dentistry, 2025)
Introduction: The loss of anterior teeth can lead to aesthetic, phonetic, and functional issues. A lithium disilicate adhesive bridge can be a good alternative and a viable compromise in cases of anterior tooth loss. The advantages include minimally invasive preparation, adhesive system, better retention, and aesthetics compared to metal materials. Removable orthodontic treatment is a preliminary option for cases of minor tooth malposition to achieve an ideal dental arch. This case report describes the management sequence for a missing incisor with tooth malposition using removable orthodontic appliances and modified design adhesive bridge. Case report: A 19-year-old female patient visited Dental Hospital Universitas Padjadjaran, Bandung with an issue of missing left central incisor due to traffic accident, and the right central incisor being in a crossbite position. The patient wanted to use a fixed dental prosthesis to improve her appearance but had not yet undergone correction for the misaligned tooth. Discussion: The patient was provided with a temporary removable dental prosthesis with removable orthodontic modifications including the addition of bite risers. Subsequently, a modified design adhesive bridge with lithium disilicate material was planned. Conclusion: The combination of removable orthodontic treatment with a final restoration utilizing a modified design adhesive bridge using lithium disilicate material for the upper anterior teeth can enhance patient satisfaction by addressing aesthetic concerns and improving phonetic function and chewing ability.